Re-searching transitions in Indian history
1 online resource (252 pages)
Keywords: The idea of transitions in Indian history emerged early when the term ‘transition’ denoted shifts from one period to another. The notion of transition itself has moved beyond being primarily economic to include dimensions of society, culture and ideology. This volume brings together scholarly works that re-examine and re-define the concept of transition by looking into a range of subjects including religion, culture, gender, caste and community networks, maritime and mercantile modes, ideas of nationalism and historiographies across geographical and temporal settings. Alterations in Indian Mercantile Modes from the Pre-modern to the Modern PeriodAnother Transition Debate? Charting the Movement Towards the Early Medieval and Out of ItEvolution of Political Institutions and Culture in Karnataka, 4001300 CEIntroduction of the British Consular Jurisdiction into Zanzibar: Indian Merchants in a Judicial TransitionMarathi Theatre in TransitionRelocating Caste: The Politics of Communalism in Early 20th-Century BombayShaming the Self, Negating History: Advent of Evangelicals and Transformation of a Community in Colonial North East IndiaTransitions in Early Tamilakam: Gender and ReligionTransitions in Malabar: Rethinking HistoryWith contributions by leading scholars from South Asia, this book will be useful to scholars and researchers of ancient history, modern Indian history, sociology and social anthropology, and South Asian studies.